Morphology and stable isotope analysis demonstrate different structuring of bat communities in rainforest and savannah habitats. Issue 12 (19th December 2018) - Monadjem, Ara; Kane, Adam; Taylor, Peter; Richards, Leigh R.; Hall, Grant; Woodborne, Stephan
Abstract : Bats play important ecological roles in tropical systems, yet how these communities are structured is still poorly understood. Our study explores the structure of African bat communities using morphological characters to define the morphospace occupied by these bats and stable isotope analysis to define their dietary niche breadth. We compared two communities, one in rainforest (Liberia) and one in savannah (South Africa), and asked whether the greater richness in the rainforest was due to more species 'packing' into the same morphospace and trophic space than bats from the savannah, or some other arrangement. In the rainforest, bats occupied a larger area in morphospace and species packing was higher than in the savannah; although this difference disappeared when comparing insectivorous bats only. There were also differences in morphospace occupied by different foraging groups (aerial, edge, clutter and fruitbat). Stable isotope analysis revealed that the range of δ 13 C values was almost double in rainforest than in savannah indicating a greater range of utilization of basal C3 and C4 resources in the former site, covering primary productivity from both these sources. The ranges in δ 15 N, however, were similar between the two habitats suggesting a similar number of trophic levels. Niche breadth, as defined by either standard ellipse area or convex hull, was greater for the bat community in rainforest than in savannah, with all four foraging groups having larger niche breadths in the former than the latter. The higher inter-species morphospace and niche breadth in forest bats suggest that species packing is not necessarily competitive. By employing morphometrics and stable isotope analysis, we have shown that the rainforest bat community packs more species in morphospace and uses a larger niche breadth than the one in savannah.